A garantia dos direitos à saúde de travestis e transexuais em serviços de saúde de Curitiba/PR: uma análise das práticas de profissionais da saúde - Baccarim, Roberta Cristina Gobbi (2017)
Although there are public policies aimed at guaranteeing the right to integral health care for transvestites and transsexuals, research shows that there are many difficulties that this population faces when seeking care by the Unified Health System. This research sought, through interviews with health professionals of Curitiba/PR, to analyze the programmatic dimension of vulnerability to illness of transvestite and transsexuals. Individual and semistructured interviews with generative questions were conducted, addressing the health professionals' knowledge about transsexuality and transvestities, public health policies for transvestites and transsexuals, and care experiences. For the analysis of the data, the analysis of the discursive practices of health professionals was used through the conceptual categories: acceptability, accessibility, quality and availability. Subsequently, the results were analyzed in order to understand if practices increase or decrease the programmatic vulnerability of transvestites and transsexuals to illness, according to the vulnerability and human rights framework. It was observed that, except for the social name use policy, health professionals do not know the health policies for transvestite and transsexual population; and that they did not have any qualification on the integral health of transvestites and transsexuals. Through the study of gender norms and the heteronormativity of queer theory, it can be related that these directly affect the practice of health policies in services and care for transvestites and transsexuals, increasing the programmatic vulnerability to illness and, consequently, social and individual vulnerabilities